Pemberdayaan Kelompok Wanita Tani Jakwire Tegal melalui Pengolahan Hasil Budidaya Jamur Tiram menjadi Penyedap Rasa Pengganti MSG - Adevia Maulidya Chikmah; Umi Baroroh; Intan Mayasari (LPPM Akbid Harapan Ibu Pekalongan, 2022)
The Jakwire Tegal Women Farmers Group is a KWT that was established in 2019 in the Margadana Village, Tegal City. There are 30 members of KWT Jakwire Tegal. The available land is still small, namely 48 m2, and 12 m2 is used for oyster mushroom cultivation. Utilization of oyster mushroom cultivation has only been running for 1 year. In order to carry out the dharma of community service, the author conducts community empowerment by utilizing the land that will be socialized in the activities of Empowering Women Farmer Groups of Jakwire Tegal Through Processing Oyster Mushroom Cultivation Products into Flavoring Substitutes for MSG. The purpose of this community service is to increase mother's knowledge about home mushroom cultivation, mushroom broth as a substitute for MSG and processing of mushroom cultivation.The method of this activity is trainingwhich consists of several stages, namely survey, training and monitoring and evaluation.The results of this activity are mThe increased understanding of oyster mushroom cultivation at home and farmer groups can make the processing of oyster mushroom cultivation into mushroom broth as a substitute for MSG.